The Role of Community Participation in the Regional Budget Preparation Process to Encourage the Realization of Good Governance - Ibrohim; Wiji Febriyani Rizkiyah (Public Service: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The realization of good governance is the hope of all parties. Government and development processes will be more effective, efficient and accountable if supported by high participation from the community. This paper seeks to explain the role of public participation in the preparation of regional budgets so far.  The success of preparing/planning regional budgets and their implementation depends on active community involvement. Regional budget planning has so far not been fully able to stimulate and expand the active involvement of these communities. The preparation of regional budgets should reflect and be aimed at achieving goals in accordance with community interests.